Assessing the efficacy of frankincense extract as a root canal irrigant against Enterococcus faecalis - Rahaf A. Almohareb; Reem M. Barakat; Eltayeb E.M. Eid; Albandari Aldaws; Nourah Alhagbani; Reham Almubayi; Dhuha Alsuwaid; Fahda N. Algahtani (PLoS ONE, 2025)
Frankincense resin exhibits antibacterial potential against various microorganisms, but little is available on its effectiveness against dental root canal biofilm. This study aimed to assess its efficacy as a root canal irrigant against Enterococcus faecalis biofilm. A standard E. faecalis strain underwent antibacterial sensitivity testing with frankincense derived from Boswellia sacra Flück and Boswellia frereana Birdw trees. Frankincense, demonstrating inhibition of bacterial growth, was further evaluated as an irrigant. Root canals of 50 single-canalled human teeth were prepared, then contaminated with E. faecalis and placed into three groups: Group A was irrigated with saline (negative control), Group B was irrigated with 5.25% sodium hypochlorite (NaClO), and Group C was irrigated with frankincense. Microbial sampling pre- and post-irrigation was conducted under aseptic conditions. Colony count reduction percentages were calculated, and the data was analyzed using one-way analyses of variance followed by Tukey’s post-hoc test (significance level set at 5%). The antibacterial susceptibility test revealed that only Boswellia sacra Flück frankincense was effective against E. faecalis. Both NaClO and frankincense significantly reduced colony counts compared to saline (p <  0.0001), with no difference between frankincense and NaClO irrigation. Therefore, root canal irrigation with B. sacra frankincense proved as effective against E. faecalis biofilm as NaClO. Further exploration of its potential as a root canal irrigant is recommended.